Contextual Teaching Learning Strategies Through The Anime Movie "Bhineka Tunggal Ika" For Enhancing Student Learning Motives - Rasimin, R.; Luthfi, Muhammad; Nurchamidah, N.; Syafaruddin, Baso (Golden Ratio of Social Science and Education, 2022)
This research was conducted based on complaints about online learning, which seemed monotonous. There was no element of attraction to motivate students' enthusiasm for learning by improvising a contextual learning model of learning through the animated film "Bhineka Tunggal Ika" in the social studies subject with the theme of the ethnic and cultural diversity of Indonesia, Class 4th MI Tsamrotul Wathon Gondosari Kudus. The researcher used the classroom action research method with pre and post-implementation tests based on knowing the actual conditions when learning was carried out. Then the data collection uses qualitative methods by prioritizing interviews and triangulation because researchers are not oriented to learning outcomes but how the learning process can be carried out optimally to foster student motivation. The results of this study are learning responses that seem interesting so that students feel happy and can explain in their language. And support from several informants will be applied in other maps tailored to the theme. The implementation of online learning is carried out by implementing anime-movie shows that contain high educational value to provide material to students with fun and reach the target. As an educator, you should have good creativity in order to create learning that will be given to students.